2002
DOI: 10.1177/13670069020060030601
|View full text |Cite
|
Sign up to set email alerts
|

Developing vowel systems as a window to bilingual phonology

Abstract: This study examines the vowel systems of German-Spanish bilingual children in order to determine whether there is interaction between the two language systems. German has a larger vowel inventory than Spanish and also contains an opposition between long and short vowels. Given the differences in the vowel systems, which point to a more marked system in the case of German, two predictions are considered: (a) bilingual children will acquire the vowel length contrast in their German productions later than monolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 12 publications
3
65
0
1
Order By: Relevance
“…Table 22 has shown that Arabic core cluster are acquired first and Arabic reversals are acquired the last. This delayed production of the marked forms was evidenced in other studies on monolingual children (Elbert, Dinnsen, & Powell, 1984;Gierut, 1999) as well as bilingual children (Keffala, Barlow & Rose, 2016;Kehoe, 2002;LIeo and Cortes, 2013).…”
Section: Figure 1 C1c2cvc1c2supporting
confidence: 65%
“…Table 22 has shown that Arabic core cluster are acquired first and Arabic reversals are acquired the last. This delayed production of the marked forms was evidenced in other studies on monolingual children (Elbert, Dinnsen, & Powell, 1984;Gierut, 1999) as well as bilingual children (Keffala, Barlow & Rose, 2016;Kehoe, 2002;LIeo and Cortes, 2013).…”
Section: Figure 1 C1c2cvc1c2supporting
confidence: 65%
“…Like Kehoe (2002), they found that German-Spanish bilinguals' acquisition of long vowels in German was delayed. The Spanish vowel system does not use a length contrast.…”
Section: Current Studymentioning
confidence: 93%
“…For instance, Caramazza, Yeni-Komshian, Zurif, and Carbone (1973), Flege and Eefting (1987), Port and Mitleb (1983) among others found voicing contrasts and VOT to be different in L1 and L2 speech. Flege, Schirru, and MacKay (2003), Kehoe (2002), Flege, Bohn, and Jang (1997) investigated the differences between L1 and L2 vowel production. Flege, Takagi and Mann (1995) investigated the differences in production and perception of liquid sounds in L1 and L2 speech.…”
Section: Contribution Of Segments and Prosody To Foreign Accentmentioning
confidence: 99%